Rabbani's Brand Ambassador Influence the Purchasing Decisions during Covid 19 Pandemic - Fauziah Yanis (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
CV. Rabbani Asysa or better known as Rabbani is a garment company that produces Muslim clothing for men, women, children and adults. With its brand â€œProfessor Kerudung Indonesiaâ€. Rabbani is the first company to produce the first and largest instant headscarves in Indonesia.In the current Covid 19 pandemic, many companies have gone out of business because they cannot maintain their market share and marketing. Moeslim clothing or fashion is one of the sectors that has been hit by the Covid-19 pandemic. Last Eid holiday was supposed to be the peak seasons for Muslim fashion, but due to the pandemic the expected results were not suitable. Fortunately, the Muslim fashion brand Rabbani has loyal resellers who helped boost sales to customers last Eid. However, Rabbani persisted by marketing its Muslim fashion products both through social media and online web using brand ambassadors as an attraction for buyers, so that the sale of Muslim products was still in demand by consumers.Rabbani used teenage Brand Ambassadors namely Fatin Sidqia and Arafah Rianti at the end of 2016 until now, in line with Rabbani's motto of making Muslim fashion into the world of fashion and embracing all Muslim circles, especially teenagers dressed in Muslim according to Islamic law. Rabbani hopes that by choosing Fatin and Arafah as brand ambassadors it can inspire young people in Indonesia to continue to work and shape their respective successes without having to put aside their religious side.This research uses quantitative methods.Independent variable (X) as Brand Ambassador and the dependent variable (Y) as a Purchase Decision.Conclusion of the reserch isbased on a hypothesis analysis of the Rabbani buyer population for the period January to October 2020. which is 7980 buyers, a sample of 99 respondents was obtained. Characteristics of respondents based on gender are all 99 female respondents. When viewed from the results of the sex characteristics of the respondents, all of them are filled by women. This shows that the buyer's decision on Rabbani products during the current pandemic is made from the brand ambassador and online either on social media or on Rabbani's website.